The prevalence of oropharyngeal squamous cell carcinoma in patients admitted with symptoms of peritonsillar abscess or cellulitis: A retrospective multicentre study. (24th August 2021) - Lau, Andrew S.; Milinis, Kristijonas; Roode, Mila; Williams, Stephen P.; Cook, Colette; Walijee, Hussein; Zammit, Matthew; Siau, Richard; Emerson, Hannah; Wright, Rosanna; Hampton, Thomas
Abstract: Objectives: Anecdotal evidence suggests that oropharyngeal squamous cell carcinoma (OPSCC) should be suspected in patients presenting with symptoms of peritonsillar abscess (PTA) or cellulitis (PTC). The aim of this study was to estimate the prevalence of OPSCC in patients presenting with symptoms of PTA/PTC. Method, Setting and Participants: We retrospectively identified all adults with a coded diagnosis of PTA or PTC who presented between 2012 and 2016 inclusive, across six ENT units in Merseyside. Records were compared to that of the centralised regional head and neck cancer database. The clinical records of a subset of patients were reviewed for the purposes of data validation. Results: A total of 1975 patients with PTA/PTC were identified. Three patients were subsequently diagnosed with OPSCC. None of the three actually had an objective underlying diagnosis of PTA/PTC on the same side. The prevalence of OPSCC in patients admitted with symptoms of PTA/PTC was 0.15% or approximately 1:650 admissions. The records of 510 patients who presented over a one‐year period (2016) were reviewed in even greater detail. There were 298 patients with PTA (59.4%) and 151 with PTC (29.1%) and 61 had an alternative diagnosis (11.9%). High‐risk features (age ≥40, tonsillar asymmetry or tonsillar lesion) were present in 106 patients (24%). Urgent follow‐up was expedited for 77 patients (73%). Conclusion: This study estimates the risk of OPSCC in patients with peritonsillar symptoms. The prevalence is low, even in a region with a relatively heavy disease burden. Clinicians should, however, retain a high level of suspicion in patients with persistent symptoms.